Institutional Factors and the Cost of Capital - Kędzior, Dorota; Kędzior, Marcin (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The article presents and critically analyses selected institutional factors affecting the cost of capital for enterprises. The paper presents the theoretical determinants of the cost of capital, the most important methods of determining this cost, and the relationship between it and risk. Selected institutional factors affecting the cost of capital were analysed. Legal systems, the development of stock exchanges, the development of the banking sector and the quality of accounting standards were recognised as the most important institutional factors. Analysis of the subject literature was the basic research method employed.